FREQUENCY AND FACTORS LEADING TO HELICOBACTER PYLORI INFECTION AMONG DYSPEPTIC PATIENTS. A SINGLE CENTRE STUDY - Ali, Saira Muhammad; Farrukh, Syed Zea Ul Islam; Haqqi, Syed Afzal Ul Haq; Siddiqui, Arif Rasheed; Sadiq, Muneer; Niaz, Saad Khalid (Journal of Ayub Medical College Abbottabad, 2022)
Background: Helicobacter pylori is infecting 50 percent or more of the world’s population, putting it the most ubiquitous infection on the world. This study is done with the objective to determine the frequency and risk factors of Helicobacter pylori infection among dyspepsia patients at Patel Hospital Karachi. Methods: This cross-sectional study was conducted at the gastroenterology department at the Patel Hospital in Karachi from 10th Jan to 10th July 2021. All patients with dyspepsia for at least 6 months having age 20-60 years of either gender were included. Three samples from stomach (2 from antrum,1 from corpus) for biopsies were collected from each patient. The specimen was sent to the microbiology department of the hospital and was reported as having histopathological confirmation of Helicobacter pylori infection. Results: Of 111 patients with dyspepsia, mean age of the patients was 44.19±16.41 years. Most of the patients (n=65, 58.6%) were males and 46 (41.4%) were females. The mean duration of dyspepsia was 11.48±5.53 months. Helicobacter pylori was discovered to be present in 93 percent of individuals (83.8 percent). The odds of Helicobacter pylori infection were found to be 7.99 times higher among patients over 40 years old (AOR: 7.99, 95 percent CI: 2.02-31.64, p: 0.003), 3.93 times higher among patients with >9 months of dyspepsia (AOR: 3.93, 95 percent CI: 1.09-14.16, p: 0.036), and 11.85 times higher among smokers as compared to non-smokers (AOR: 11.85, 95 percent CI: 1.42-99.08, p-value 0.023). Conclusion: The rate of Helicobacter pylori infection in patients with dyspepsia was found to be higher. Furthermore, increasing age, increase duration of dyspepsia and smoking is found to be independent risk factors.